A Multidisciplinary Tool for the Development of a Regional-scale Geotechnical Model: A Case Study in the North-Western Adriatic Coastal Area. (2016) - Tonni, Laura; Rocchi, Irene; Cruciano, Nadia Pia; Martínez, María F. García; Martelli, Luca; Calabrese, Lorenzo
Abstract: The paper describes the geotechnical model of a coastal flat area facing the Adriatic Sea, between the municipalities of Cesenatico and Bellaria-Igea Marina (Emilia-Romagna region, Italy). On the basis of a large experimental database provided by the Geological, Seismic and Soil Survey of the Emilia-Romagna Authority, a stratigraphic scheme of the upper 40 m of this coastal plain subsoil has been defined and reliable estimates of parameters for the different soil units have been derived. The accurate mechanical characterization of soils, also reflecting their sedimentological framework, allows the development of a regional-scale geotechnical model providing a reliable and useful support to geotechnical engineers working in this area or similar geological environments.